2009
DOI: 10.1007/s10726-009-9180-z
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Dynamics in Partially Distributed Teams: an Exploratory Study of the Effects of Configuration and Distance

Abstract: Despite the importance of leadership and the wealth of empirical studies focused on leadership effectiveness in traditional and computer-supported groups, there is little research examining leadership dynamics in partially distributed virtual teams (PDTs). Virtual teams are partially distributed when they are configured with one or more subgroups of collocated members and isolated members. This paper lays the groundwork for an in-depth study of leadership in PDTs that can be extended to other types of virtual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…Consistent with prior early-stage research on virtual teams (e.g., Carte et al, 2006;Cogliser et al, 2012;Ocker et al, 2011), we studied the interactions among members (n = 152) of vPDTs (n = 28) organized for an undergraduate business class project. The team members were geographically dispersed between two universities (one in the US and one in the UK) in order to encourage virtual communications.…”
Section: Partially Distributed Teams 19mentioning
confidence: 89%
See 1 more Smart Citation
“…Consistent with prior early-stage research on virtual teams (e.g., Carte et al, 2006;Cogliser et al, 2012;Ocker et al, 2011), we studied the interactions among members (n = 152) of vPDTs (n = 28) organized for an undergraduate business class project. The team members were geographically dispersed between two universities (one in the US and one in the UK) in order to encourage virtual communications.…”
Section: Partially Distributed Teams 19mentioning
confidence: 89%
“…Ocker et al (2011) described three different characteristics that tend to exacerbate this so-called "in-group" effect. The characteristics -all of which are common to temporally dispersed vPDTs -include geographic distance, temporal distance, and cultural distance (including both organizational and national culture).…”
Section: Subgroupsmentioning
confidence: 99%
“…Research has found that training and leadership styles can mitigate some of the negative effects associated with subgroup formation [34,35]. Managers may want to take an active lead in heading off potential problems associated with racial and gender diversity resulting from subgroup formation.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…That is, there is at least one subgroup consisting of co-located members, while other team members are geographically dispersed from this subgroup (although they may be co-located with each other). For members and subgroups that are geographically separated, there is a required reliance on electronic means for communication 15 . Figure 1, shown below, represents one of the types of partially distributed team configuration that could occur.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to be able to engage all the students and give them exposure to how projects work in the real world, once they graduate, many professors get the students involved on group projects and expect the workload to be distributed evenly (Ocker & Huang, 2011). Professors choose to do this because in most high tech/engineering jobs today, the teams are partially or completely virtual teams, so as to have an access to an expanded pool of workers at the best possible salaries 11 .…”
Section: Literature Reviewmentioning
confidence: 99%